Immune-checkpoint inhibition in first-line treatment of advanced non-small cell lung cancer patients: Current status and future approaches. (April 2017) - Remon, J.; Pardo, N.; Martinez-Martí, A.; Cedrés, S.; Navarro, A.; Martinez de Castro, A.M.; Felip, E.
Highlights: PD-L1 status should be considered a new a new predictive biomarker in advanced NSCLC. Upfront Immunotherapy is standard treatment in a subgroup of NSCLC patients. Efficacy of these treatments according to the range of different PD-L1 expression remains unclear. Abstract: Immune checkpoint inhibitors are considered standard second-line treatment in advanced non-small cell lung cancer patients. This strategy has also become standard in first-line setting for a subgroup of patients with strongly positive PD-L1 tumors; therefore, PD-L1 status might be considered a new biomarker that deserves upfront testing. New combinations of immune checkpoint inhibitors and with chemotherapy have been tested in first-line treatment. However, some questions remain unanswered such as the best treatment strategy or the real upfront efficacy of these therapeutic strategies in the whole lung cancer population. In this review we summarize the main results in the first-line setting of recent phase III trials with immune checkpoint inhibitors in advanced non-small cell lung cancer patients.